1987
DOI: 10.1007/bf00757163
|View full text |Cite
|
Sign up to set email alerts
|

Selecting a rating scale for evaluating services to the chronically mentally Ill

Abstract: A multi-attribute utility analysis employing ideal outcome measure criteria was applied to seven brief rating scales in order to identify the best performing instrument. A variety of judgmental data were collected from therapists working in mental health service agencies and from evaluation research experts to contrast the performance of the seven rating scales on criteria for selecting outcome measures developed by an NIMH task force. Transformations of the performance data were weighted in accordance with pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
42
0

Year Published

2003
2003
2019
2019

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 84 publications
(43 citation statements)
references
References 7 publications
1
42
0
Order By: Relevance
“…Moreover, the CSI scores were able to differentiate between individuals who reported a need for mental health services and those who did not. CSI was designed to function as a brief self-report measure of psychiatric symptoms (Ciarlo and Edwards 1981;Green and Gracely 1987). Given the demands in mental health practice settings, a 5-min psychiatric interview such as the CSI is a major advantage in its utilization as a measure of prevalence of psychiatric symptoms.…”
Section: Methodsmentioning
confidence: 99%
“…Moreover, the CSI scores were able to differentiate between individuals who reported a need for mental health services and those who did not. CSI was designed to function as a brief self-report measure of psychiatric symptoms (Ciarlo and Edwards 1981;Green and Gracely 1987). Given the demands in mental health practice settings, a 5-min psychiatric interview such as the CSI is a major advantage in its utilization as a measure of prevalence of psychiatric symptoms.…”
Section: Methodsmentioning
confidence: 99%
“…Other commonly cited features included feasibility, appropriate case-mix adjustment, and sensitivity to change. From a researcher perspective, these are key factors to consider in the mental health-care quality assessment (Burlingame et al, 2005;Burlingame et al, 1995;Erbes et al, 2004;Green & Gracely, 1987;Hermann et al, 2006;Hermann et al, 2004;Hermann & Palmer, 2002;Lambert et al, 1992;Slade, 2002;Waraich et al, 2010).…”
Section: Existing Frameworkmentioning
confidence: 99%
“…This feature was only cited by two of the ten frameworks, both of which dis-cussed usefulness in the context of utility across settings (Erbes et al, 2004;Green & Gracely, 1987). Conversely, the clinician-participants framed usefulness in terms of improving client engagement, program evaluation, session-by-session feedback, prevention of drop-out, and creating focus in therapy.…”
Section: Initial Motivation and Selecting Measuresmentioning
confidence: 99%
“…for this population. 77 Interviewer ratings of work, independent living, and social functioning from the RFS were used for this study in accordance with procedures previously reported.15 After interview training, the ICC among 3 interviewers on the RFS items was >0.8. A principal components factor analysis of the 3 items found that there was a single factor with an eigen value greater than 1 that explained 55% of the item variance, lending credence to the use of the global score.…”
mentioning
confidence: 99%